The Linguistic Construction of Conformity: A Critical Analysis of Ideological and Multimodal Discourse - Theodoropoulos, Emil; Tsakanika, Stavroula; Boleti, Ioanna (International Journal of Language and Literary Studies, 2026)
This article examines how normalcy is produced and naturalized through linguistic and multimodal discourse practices, using Bernardo Bertolucci’s The Conformist (1970) as its case study. Grounded in Fairclough’s Critical Discourse Analysis (CDA) and social semiotics, the methodology involves a qualitative analysis of selected scenes to explore how dialogue, image, body posture, and spatial organization interact to reinforce the film’s ideological framework. The findings demonstrate that the film articulates a model of normalcy grounded in discipline, conformity, and exclusion. Linguistically, this is achieved through generalizations, impersonal constructions, and moralized vocabulary that frame conformity not as a choice but as a universal necessity for stability. Multimodally, the film’s visual architecture encodes bodily regulation and containment, while the construction of the “Other”—specifically political dissidents and gender-nonconforming figures—serves to legitimize the authoritarian order. Ultimately, the article argues that tensions between the verbal and visual layers generate critical ruptures that expose and destabilize the mechanisms through which fascist imaginaries are normalized, positioning the film as a vital resource for developing critical language and visual literacy.